2020
DOI: 10.1109/tsg.2019.2962269
|View full text |Cite
|
Sign up to set email alerts
|

Centralised and Distributed Optimization for Aggregated Flexibility Services Provision

Abstract: The recent deployment of distributed battery units in prosumer premises offer new opportunities for providing aggregated flexibility services to both distribution system operators and balance responsible parties. The optimization problem presented in this paper is formulated with an objective of cost minimization which includes energy and battery degradation cost to provide flexibility services. A decomposed solution approach with the alternating direction method of multipliers (ADMM) is used instead of common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 42 publications
(64 reference statements)
0
32
0
Order By: Relevance
“…ere are many early studies done on the method of multipliers and ADMM [63,64]. Some recent studies done on ADMM can be found in [65][66][67][68][69]. In [65], Erseghe has proposed a fully distributed algorithm for optimal power flow using ADMM.…”
Section: Alternating Direction Methods Of Multipliersmentioning
confidence: 99%
See 1 more Smart Citation
“…ere are many early studies done on the method of multipliers and ADMM [63,64]. Some recent studies done on ADMM can be found in [65][66][67][68][69]. In [65], Erseghe has proposed a fully distributed algorithm for optimal power flow using ADMM.…”
Section: Alternating Direction Methods Of Multipliersmentioning
confidence: 99%
“…In this paper, the author has introduced another variation on ADMM Algorithm 1 with assumptions such as g(y) � 0, where y is contained in a linear space with associated orthogonal projector and also with certain assumptions on initial choices. In the study [66], authors have presented a decomposed solution approach with ADMM to solve a cost minimization problem, where the objective consists of energy and battery degradation cost. is work has used a modified version of ADMM, which helps to reduce the computations cost and ensures the stability of the solution.…”
Section: Alternating Direction Methods Of Multipliersmentioning
confidence: 99%
“…Prosumers could also trade their flexibility with an upstream entity such as an aggregator. Reference [82] proposed a method to provide flexibility services for aggregators in large-scale energy communities. A bottom-up decentralized approach has been used for trading energy among customers and aggregators in [83][84][85].…”
Section: Flexibilities Related Trading At Customer Levelmentioning
confidence: 99%
“…Even if a centralized optimization offers the best optimality assurances [7], it comes to be intractable for a high number of batteries, mainly due to the high number of discrete variables and to requirements related to the memory and computational time [10]. Some authors also consider the requirement to not disclose the local private information of each user participating in the aggregation [10][11][12] The authors in [10] propose a distributed methodology for the optimal coordination of Distributed Energy Resources (DERs). The proposed MILP approach is based on Dantzig-Wolfe decomposition and column generation.…”
Section: Introductionmentioning
confidence: 99%
“…Other researches propose methods to achieve the scalability of a large number of storage devices [12,13] and assume that the system operator evaluates, also based on operating costs, the required flexibility to solve a problem in the distribution or transmission system and that it is supported by an aggregator. In [12] the alternating direction method of multipliers (ADMM) is proposed for furnishing energy flexibility to the DSO considering the optimal operation of one hundred prosumers. Flexibility requests are sent by the DSO to the aggregator that should determine the best solutions for achieving the flexibility request while reducing the operational costs.…”
Section: Introductionmentioning
confidence: 99%